MILIARY TUBERCULOSIS AND ELEVATED TRANSAMINASE ENZYMES IN AN UNTREATED HUMAN IMMUNIDEFICIENCY VIRUS (HIV) PATIENT: A CASE REPORT: To Identify and Treat It Comprehensively - Veronica, R.Merlinda; Azis, Abdurrahman; Indri, R.Melda; Simanjuntak, Arya Marganda (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2024)
Introduction Tuberculosis (TB) is closely related to Human Immunodeficiency Virus (HIV) and causes 25% death in HIV patients. Miliary TB is a complication of a focus of tuberculosis infection that is spread hematogenously, in the form of fine spots that are generally evenly distributed throughout the lung fields. Giving Anti Tuberculosis Drugs can have side effects in some TB patients including drug-induced hepatitis, therefore it is necessary to check liver function. Liver function tests that are commonly used are transaminase enzymes, namely SGOT and SGPT levels which will show an increase if there is damage or inflammation in liver tissue. In HIV positive patients, it is recommended to have liver function tests every month. Case illustration Here we report a case of a male patient diagnosed with miliary TB and HIV who had an increase in the transaminases enzyme at the beginning of the diagnosis with chief complainnts of cough with phlegm, fluctuating fever, night sweats, weakness, nausea, vomiting, and weight loss 0f 14 kg since three months before being admitted to the hospital. The patient appeared moderately ill with composmentis consciousness, temperature 38,8C, saturation 98% with oxygen, BMI underweight (13,4kg.m2), anemic conjunctiva and sclera are not icteric. The laboratory finding anemia left shift hypochromic microytic with thrombocytopenia (Hb 9,8g/dl, Hematocrit 28,3%, leukocytes 2470/Ul, platelets 157000/uL MCV 87fl, MCH 28,7pg, MCHC 33,0g/dl), increase transaminase enzymes (SGOT:398U/L SGPT:90U/L), hypoalbuminemia (2,17g/dL), normal kidney function, hiponatremia (124), HbsAg and Anti HCV: non Sputum BTA I/II/II: +1/+2/+2, Gene Xpert: MTB detected, Rifampicin resistance was not detected. Reactive HIV test, CD4: 26 sel/UL. Ro Thorax examination: Inhomogeneous nodular opacity in both lung fields, suspected pneumonia, USG: Chronic liver disease. The patient received Co-trimoxazole therapy, modified Anti Tuberculosis Drugs and Antiretrovirals. After being given modified anti-tuberculosis and antiretroviral therapy, clinical and laboratory improvement occurred. Conclusion The need for monitoring of liver function in patients who show symptoms of hepatitis and examination of liver function.